Like we talk at home: Slovenian dialects in the family in Austrian Carinthia - Piko-Rustia, Martina (Jezikoslovni zapiski, 2018)
In 2010, the Christian Cultural Center in Klagenfurt created the initiative Slovenian in the Family, which addresses the importance of living use of Slovenian in the family environment. Slovenian in the Family is the foundation for preserving and developing ethnic minorities across the Slovenian border and around the world. The initiative uses various incentives to increase awareness of Slovenian in families as an asset that parents and grandparents can transmit to children in living form in the family and in the immediate and broader home environment.